ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI KONSUMEN DALAM MEMUTUSKAN PEMBELIAN JASA (Studi Kasus : PO. Imi Fatwa Sakti Travel Jambi) - Azizah Azizah; Hapzi Ali (Universitas Batanghari Jambi, 2009)
Fluctuation Percentage is amount of loaded chair from amount of available chair cause instability at income from operation and earnings. Fluctuation inPO. IFS Travel Jambi because of factor is lack of consumer motivation to do purchasing of service and lack activity of promotion. For company which active in transportation service, primary factor in most consumer in self stand a chance to cause sale volume fluctuation is the lack of consumer motivation do purchasing.In this research to know consumer motivation in doing purchasing atPO. IFS Travel used by Theory attributes Motivate Maslow or which is ordinary to be recognized with Hierarchy need of Maslow namely need of physiological, security need, social need, appreciation need, and self actualication need. Key Word : Motivation, Hierarchy need theory of Maslow.